The Timing of Product Innovation and Regulatory Delay - James E. Prieger (University of California, Department of Economics, 2003)
This paper endogenizes the interplay between innovation by a regulated â?rm and regulatory delay. In the signaling model, the â?rm times its innovation to communicate its private information about the MC of delay to the regulator. When product innovation costs fall over time, an extra day of regulatory delay increases time to introduction by more than a day. Successful signaling leads the regulator to adjust regulatory delay. The separating equilibrium of the signaling model generates testable predictions for how innovation and regulatory delay evolve over time. The model is consistent with data gathered from one of the Bell telecommunications â?rms.
Keywords: 330